Oral rehabilitation with dental implant and immediate loading by guided surgery: case report (Research, Society and Development, 2021)
Edentulism is an extremely frequent challenge in the dentist's daily routine. The search for functional and aesthetic solutions for these cases has led to several innovations in the dental materials market, such as osseointegrated dental implants, prostheses, crowns and surgical guides. The improvement of materials and methods in Implantology brought possibilities for intervention, which through digital planning and preparation of 3D surgical guides, grant less work time to offer the patient greater comfort through less invasive and bloody techniques, with the purpose to reestablish the patient's function, aesthetics and biopsychosocial condition. This clinical case aims to describe the planning and installation of immediate dental implant morse cone (Drive, Neodent®, Curitiba, Brazil) using the technique with 3D surgical guide (3D Studio - Virtual Face Planning®, Natal-RN, Brazil), planned through cone beam computed tomography analyzed using Blue Sky Bio LLC software (Libertyville, Illinois), in addition to grafting with bovine mineral bone structure (Lumina-Bone Fino, Criteria®, SP- São Paulo, Brazil) followed by unitary crown and installation of immediate load in aesthetic area.